Walking with UAN.GO Exoskeleton: Training and Compliance in a Multiple Sclerosis Patient - Gianluca Sesenna; Cecilia Calzolari; Maria Paola Gruppi; Gianluca Ciardi (MDPI AG, 2021)
Background: Multiple sclerosis is a progressive neurodegenerative disease that affects myelin in the central nervous system. It is complex and unpredictable and occurs predominantly in young adults, causing increasing disability and a significantly lower quality of life. Recent studies investigated how rehabilitation training through the use of a robotic exoskeleton can influence walking recovery in patients with a serious neurological disease. Aim: The purpose of this study was to analyze the first approach of a multiple sclerosis patient to a robotic exoskeleton for the lower limbs, in order to assess the effectiveness of the protocol on walking ability, adaptability of the device, level of appreciation, variations in parameters related to walking, and fatigue perception. Methods: This study was conducted on a 71-year-old male diagnosed with primary progressive multiple sclerosis since 2012, with an EDSS score of 6. The patient underwent a cycle of 10 sessions of treatment with the exoskeleton for the lower limbs, the UAN.GO, lasting 1 h 30 min. Pre- and post-treatment evaluations were carried out with the 6 min walking test, the Fatigue Severity Scale, the Short Form-36 Health Survey, and a Likert scale for review. During each session, blood pressure, heart rate, and peripheral saturation were monitored; in addition, the perception of fatigue by the Borg scale was studied. Result: A comparison between the initial and final evaluations showed improvements in the walked distance at 6 MWT (T0 = 53 m/T1 = 61 m). There was a positive trend in saturation and heart rate values collected during each session. Further improvements were found by the Borg scale (T0 = 15/T1 = 11). Discussion: The data collected in this case report show promising results regarding the treatment of multiple sclerosis patients with the UAN.GO exoskeleton, with benefits on both motor performance and vital parameters.